3D printed gyroid scaffolds enabling strong and thermally insulating mycelium-bound composites for greener infrastructures - Deepak Sharma; Hortense Le Ferrand (Nature Communications)
Abstract Mycelium-bound composites (MBCs) grown from fungi onto solid lignocellulosic substrates offer a sustainable alternative to petroleum-based materials. However, their limited mechanical strength and durability are often insufficient for practical applications. In this work, we report a method for designing and developing strong and thermally insulating MBCs. The method grows mycelium onto 3D-printed stiff wood-Polylactic Acid (PLA) porous gyroid scaffolds, enhancing the strength of the scaffold while imparting other functional properties like thermal insulation, fire resistance, hydrophobicity, and durability. The extent of improvement in MBCs’ performance is directly dependent on the mycelium growth, and the best growth is observed at 90% porosity. We observe yield strength (σy) of 7.29 ± 0.65 MPa for 50% porosity MBC, and thermal conductivity (Kt) of 0.012 W/mK for 90% porosity MBC. Maximum improvement in σy (50.4–77.7%) between before and after mycelium growth is observed at medium (70%)–high (90%) porosity. The MBCs also exhibit design-dependent improved fire-resistance and durability compared to the base wood-PLA scaffold, further enhancing their suitability for practical applications. Our findings show that integration of 3D printing, design, and biomaterials enables the development of sustainable bio-based composites to replace pollution-causing materials from the construction industry.